1991
DOI: 10.1002/ajmg.1320390422
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of hereditary motor sensory neuropathies (type I)

Abstract: Patients affected with hereditary motor sensory neuropathy (HMNS) type I were traced through hospital records. Each case was re-examined, a family history was drawn, and EMG examination was performed in those members of the family who could have inherited the trait. In the prevalence year 1987, in a population of 1,067,130 inhabitants of 2 contiguous provinces of northeast Italy, 100 living cases were recorded in 30 families, giving a minimal prevalence rate estimate of 9.37/100,000. HMSN I is inherited as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…The longest time interval investigated was 27 years (1960-1987), in the retrospective study of Mostacciuolo et al [11]. A high level of heterogeneity among studies precluded a firm conclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The longest time interval investigated was 27 years (1960-1987), in the retrospective study of Mostacciuolo et al [11]. A high level of heterogeneity among studies precluded a firm conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…When analysing the prevalence of CMT (9.37-20.1/100,000), it can be inferred that the lower prevalence rate (9.37/100,000) was reported in an older study [11], in which the only diagnostic methods were nerve biopsies and electromyography; this was also a retrospective study. The second study with the lowest prevalence was also a retrospective study [15], and diagnosis was confirmed only by clinical and CMT diagnosis established according to European CMT Consortium criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charcot-Marie-Tooth disease type 1 (CM T 1) is the most common subtype of the heredi tary motor and sensory neuropathies (HM SN) [1], the prevalence in the Italian population being 9.4/100,000 inhabitants [2], The dis ease is clinically characterized by distal mus cle atrophy and weakness, absence o f deep tendon reflexes and pes cavus. Nerve conduc tion velocity is decreased and nerve biopsy shows a hypertrophic neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Σε ορισμένους πληθυσμούς ο επιπολασμός της CMT είναι χαμηλότερος από τα πλαίσια των ποσοστών που παρουσιάζονται σε παγκόσμιο επίπεδο, όπως στη Βόρειο Ιταλία 9.4/100,000 (Mostacciuolo et al 1991;Mostacciuolo et al 1995), στη Δανία 6.06/100,000 (Werdelin and Keiding 1990), στη Λιβύη 7.9/100,000 (Radhakrishnan Ποσοστά επιπολασμού της CMT σε διάφορους πληθυσμούς et al 1987), στη Νιγηρία 0.15/100,000 (Aiyesimoju et al 1984), στην Ισλανδία 1,6/100,000 (Combarros et al 1987), στη Βόρεια Καρολίνα 5.4/100,000 (Kurtzke et al 1971) και στη Δυτική Ιαπωνία 10.8/100,000 (Kurihara et al 2002) Διάγραμμα 4.1 Ποσοστιαίες αναφορές διαφόρων πληθυσμών ανά το παγκόσμιο για τον επιπολασμό της CMT ανά 100,000 άτομα.…”
Section: επιπολασμός της Cmtunclassified